Como posso resolver a expressão [-2 . (x-1) . (x+1)] ???
adrielyfurtado645:
essa expressão é igualada à algum valor?
Soluções para a tarefa
Respondido por
1
[-2 . (x-1) . (x+1)] =
[-2(x²-1)]=
-2x²+2
[-2(x²-1)]=
-2x²+2
Respondido por
1
[-2 . (x-1) . (x+1)]
= - 2. (x² + x - x - 1)
= - 2.(x² - 1)
= - 2x² + 2
= - 2. (x² + x - x - 1)
= - 2.(x² - 1)
= - 2x² + 2
Perguntas interessantes
Administração,
10 meses atrás
Artes,
10 meses atrás
Inglês,
10 meses atrás
Matemática,
1 ano atrás
História,
1 ano atrás
Matemática,
1 ano atrás
Administração,
1 ano atrás
Matemática,
1 ano atrás